Cognitive and Psychosocial Outcomes of Self-Guided Executive Function Training and Low-Intensity Aerobic Exercise in Healthy Older Adults - Yang, Lixia; Gallant, Sara N.; Wilkins, Leanne Karyn; Dyson, Ben (Frontiers in Aging Neuroscience, 2020)
Objectives: Prior work has demonstrated that executive function training or physical exercise can improve older adults’ cognition. The current study takes an exploratory approach to compare the feasibility and efficacy of online executive function training and low-intensity aerobic exercise for improving cognitive and psychosocial functioning in healthy older adults. Method: Following a standard pretest-training-posttest protocol, 40 older adults (aged 65+) were randomly assigned to an executive function or a physical training group. A battery of cognitive and psychosocial outcome measures was administered before and after training. During the 10 weeks of self-guided training at home (25-30 minutes/day, 4 days/week), the executive function training group practiced a set of adaptive online executive function tasks designed by Lumos Labs, whereas the physical training group completed an adaptive DVD-based low-intensity aerobic exercise program. Results: Training transfer effects were limited. Relative to low-intensity aerobic exercise, executive function training yielded cognitive improvement on the Wisconsin Card Sorting Task (WCST-64), a general executive function measure. Depression and stress levels dropped following both training programs, but this could be driven by decreased stress or excitement in performing that tasks over time. Discussion: The results revealed limited cognitive benefits of the online executive function training program, specifically to a near transfer test of general executive control. Importantly, the current study supports the feasibility of home-based self-guided executive function and low-intensity physical training with healthy older adults.